Być kobietą i być mężczyzną, czy być człowiekiem po Edenie? Rdz 3,16-19 raz jeszcze przemyślane - Lemański, Janusz Adam (Verbum Vitae, 2022)
Gen 3:(14–)16–19, in the traditional interpretation, is understood as a description of the sentence for breaking God’s prohibition. The various statements contained in these verses are therefore most often all understood as punishments imposed upon the serpent (v. 14), women (v. 16), and men (vv. 17–19). The present article, however, offers and analyzes the suggestion that these statements should be interpreted only as the etiology of social realities in the times of the biblical author and as a description of the whole of humanity, encompassing both men and women, and not only the woman (suffering the pains of childbirth) or the man himself (hard work in the field, and death) in isolation.